UNCTAD Handbook of Statistics 2018 - United Nations Conference on Trade; Development (United Nations, 2018)
The UNCTAD Handbook of Statistics was first launched in 1967. Over the past 50 years, the handbook has evolved to incorporate new statistics and ensure that readers have access to the best possible information available. The 2018 edition of the Handbook continues in this tradition of excellence and innovation. This year edition introduces ’nowcasted’ estimates for total merchandised trade, total services trade and Gross Domestic Product.